2014
DOI: 10.1248/bpb.b13-00534
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin Suppresses MMP-9 Expression through Modulation of p38 MAPK Activity in Human Dermal Fibrobalsts

Abstract: We aimed to identify a novel flavonoid from the in-house natural products to suppress matrix metalloproteases (MMPs), which is responsible for degradation of collagen and other extracellular matrix proteins. Total eight natural products were screened for identification of a novel MMP-9 suppressor using MMP-9 reporter system, where the prompt initial screening with multiple samples is readily examined. Among the extracts used in the present study, one extract (Citrus unshiu) was found active in this assay syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Our data indicated that PMBPs treatment inhibited the activation of ERK1/2 and p38 MAPK in a dose-dependent manner, but had little effect on JNK pathway ( Fig 8B and 8D ). Our data here, together with others, show that MMP-9 can be activated through multiple signaling pathways including the MAPKs family [ 40 , 41 , 42 ], however, whether PMBPs directly regulated MMP-9 activity through ERK1/2 and p38 MAPK pathways needs further investigation.…”
Section: Discussionsupporting
confidence: 49%
“…Our data indicated that PMBPs treatment inhibited the activation of ERK1/2 and p38 MAPK in a dose-dependent manner, but had little effect on JNK pathway ( Fig 8B and 8D ). Our data here, together with others, show that MMP-9 can be activated through multiple signaling pathways including the MAPKs family [ 40 , 41 , 42 ], however, whether PMBPs directly regulated MMP-9 activity through ERK1/2 and p38 MAPK pathways needs further investigation.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies shown that nobiletin inhibits invasion and migration capacities of nasopharyngeal carcinoma cell lines and glioma cell lines through down-regulating ERK and/ or JNK pathway [62, 63]. Nobiletin also suppresses MMP-9 expression by reducing p38 MAPK activity [64]. Furthermore, we were interested in nobiletin's inhibitory mechanism on ERK and JNK signaling pathway that mediates MMP-2 and MMP-9 expression, implicating in U2OS and HOS cells metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are responsible for degradation of extracellular matrix proteins and collagen. NOB has been identified to a novel MMP-9 suppressor using MMP-9 reporter system through downregulation of p38 MAPK phosphorylation in human dermal fibroblasts stimulated by PMA [ 92 ].…”
Section: Miscellaneous Sectionmentioning
confidence: 99%